Synthesis and characterization of a homogeneous and silica supported homoleptic cationic tungsten(vi) methyl complex: application in olefin metathesis. Issue 75 (30th August 2016) - Dey, Raju; Samantaray, Manoja K.; Poater, Albert; Hamieh, Ali; Kavitake, Santosh; Abou-Hamad, Edy; Callens, Emmanuel; Emwas, Abdul-Hamid; Cavallo, Luigi; Basset, Jean-Marie
Abstract : We describe here a facile synthesis of a cationic tungsten-methyl complex for the application in olefin metathesis. Abstract : A method for the synthesis of a homogeneous cationic tungsten(vi )pentamethyl complex [(WMe5 ) + (C6 F5 )3 BMe − ] from neutral tungstenhexamethyl (WMe6 ) and a silica supported cationic tungstentetramethyl complex [(Si–O–)WMe4 + (C6 F5 )3 BMe − ] from a neutral silica supported tungstenpentamethyl complex [(Si–O–)WMe5 ] is described. In both cases a direct demethylation using the B(C6 F5 )3 reagent was used. The aforesaid complexes were characterized by liquid or solid state NMR spectroscopy. Interestingly, the homogeneous cationic complex [(WMe5 ) + (C6 F5 )3 BMe − ] shows moderate activity whereas the supported cationic complex [(Si–O–)WMe4 + (C6 F5 )3 BMe − ] exhibits good activity in olefin metathesis reactions.